Microvessel area of immature vessels is a prognostic factor in renal cell carcinoma. (15th August 2013) - Sato, Mototaka; Nakai, Yasutomo; Nakata, Wataru; Yoshida, Takahiro; Hatano, Koji; Kawashima, Atsunari; Fujita, Kazutoshi; Uemura, Motohide; Takayama, Hitoshi; Nonomura, Norio
<x xml:space="preserve">Abstract</x> Objectives To analyze the presence of immature vessels as a predictive factor of prognosis in patients with renal cell carcinoma. Methods Tissue samples were obtained from 50 renal cell carcinoma patients who underwent radical nephrectomy, and the blood vessels were stained using antibodies to cluster of differentiation 34 and α‐smooth muscle actin. Immature vessels were defined as those positive for cluster of differentiation 34, and mature vessels as those positive for both cluster of differentiation 34 and α‐smooth muscle actin. The extent of vascularization was quantified by calculating the microvessel area and microvessel density. Results The microvessel area of immature vessels was positively associated with tumor grade (P < 0.0001), T stage (P < 0.0001) and American Joint Committee on Cancer stage (P < 0.0001), and was significantly higher in tumors with metastasis than in those without metastasis (P < 0.0001). The microvessel density did not associate with tumor grade or T stage. The disease‐free survival and overall survival were significantly shorter in patients with high microvessel area. Conclusions The microvessel area of immature vessels seems to be associated with renal cell carcinoma aggressiveness, suggesting this might be considered as a novel prognostic factor in patients with these tumors.